Depressive symptoms of older adults with chronic diseases: the mediating roles of activities of daily living and economic burden of diseases - Ni, Zihan; Zhu, Xiuyuan; Tian, Kan; Chen, Qing; Yang, Yi; Xie, Shiyu (Frontiers in Psychology, 2024)
Objective: To explore the mediating roles of activities of daily living (ADL) and economic burden of diseases in the relationship between chronic diseases and depressive symptoms of older adults.The data were sourced from China Health and Retirement Longitudinal Study (CHARLS).The number of chronic diseases,ADL, out-of-pocket medical expenses and the Center for Epidemiological Studies Depression Scale (CES-D) were selected as measuring indexes. Mediation analysis was conducted to explore the potential mediating roles of ADL and economic burden of diseases in the association between chronic diseases and depressive symptoms.The number of chronic diseases, ADL, economic burden of diseases and depressive symptoms of older adults were significantly correlated with each other. ADL and economic burden of diseases individually mediated the relationship between the number of chronic diseases and depressive symptoms, accounting for 31.460% and 5.471% of the total effect respectively. Additionally, ADL and economic burden of diseases demonstrated a chain mediating effect in this relationship, contributing to 0.759% of the total effect. Depression 删除[Hannah]: the elderly 删除[Hannah]: 2 删除[Hannah]: Purpose 删除[Hannah]: link 删除[Hannah]: on 删除[Hannah]: the elderly 删除[Hannah]: was 删除[Hannah]: obtained 删除[Hannah]: activities of daily living ( 删除[Hannah]: Multiple linear regression was utilized to analyze the factors influencing the depression of older adults, and m 删除[Hannah]: used 删除[Hannah]: activities of daily living 删除[Hannah]: depression 删除[Hannah]:Gender age, education level, marital statusand social participation had significant effects on depression of older adults.The chain-mediated model effectively elucidated the mediating roles of activities of daily living and economic burden of diseases in the association between chronic diseases and depressive symptoms among older adults. The study underscores the need for policymakers to focus attentively on the mental health of older adults with chronic diseases. Enhancing the capacity for ADL and strengthening social security to mitigate the economic burden of diseases are recommended strategies to alleviate depressive symptoms in older adults.